1991
DOI: 10.1159/000147075
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Microscopic Studies on the Maturation of Secretory Cells in the Mouse Harderian Gland

Abstract: The porphyrins in the Harderian glands of mice are first detectable at 7–8 days of age in both sexes. Thereafter, the levels show a marked rise during the closed-eye period, reaching a peak around the time of eyelid disjunction and then decrease gradually until day 25. At onset of puberty, the level rises again and exhibits a sexual dimorphism. The development of the Harderian gland was examined by light and electron microscopy in the mouse. Although two types of secretory cells, designated as type A and type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The two types of HG secretory cells described by Shirama and Hokano (1991) were observed. A-type cells containing a greater number of larger-sized lipid vacuoles (Fig.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The two types of HG secretory cells described by Shirama and Hokano (1991) were observed. A-type cells containing a greater number of larger-sized lipid vacuoles (Fig.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Other authors have also reported an extrapancreatic inflammation, including Bernard et al (19911, Miyagawa et al (1986), and Sugihara et al (1989). The Harderian gland (HG), a large intraorbital organ found in almost all land vertebrates, contains lipids and porphyrins in the mouse (Shirama and Hokano, 1991), and to our knowledge there are no articles solely dedicated to the infiltration occurring in the HG, the salivary gland (sialadenitis) being the most studied extrapancreatic infiltration site in NOD mice. In these studies, one or several foci at peridudal and perivascular sites and retrogressive changes of some acini have been described (Goillot et al, 1991;Sugihara et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…More rapid development of the gland occurs after birth during the period of eyelid disjunction both in the differentiation of the glandular epithelium and in production of porphyrin (Shirama and Hokano, 1991).…”
Section: Mammalsmentioning
confidence: 99%
“…It becomes functional from around 14 days of age when the pups open their eyes; however, the gland continues to grow and mature until adulthood ( 32 ). We found that the size of the gland is similar in ACBP Ϫ / Ϫ and ACBP +/+ mice until just before weaning at 21 days of age ( Fig.…”
Section: Resultsmentioning
confidence: 55%